Desarrollo de una máquina de control de calidad y empacado de cucharas plásticas de la empresa "Truplast". - Chiriboga Salazar, Manuel Alejandro (2018)
TRUPLAST Company, dedicated to the production of plastics in general, seeks to satisfy one of its highest demands at the national level, improve its production, to provide customers with a quality product. Plastic utensils, such as spoons produced in cold-cast injection systems, come in ladder strips which are detached, counted, inspected and packed by hand. Due to the growth of its demand and its current system being obsolete, a quality control and packaging machine was designed and implemented for the automation of its production line of plastic spoons. The vertical type packing machine will carry out the process that contemplates a complete packaging of three seals, which consists of several sections such as the forming, sealing and shearing of the sheath, and also the product weighing system. Its electro-pneumatic system is controlled by a Panasonic PLC with a Panasonic GT02 monochromatic screen. A quality control system is implemented with which the matrices of products that are defective will be discarded. Based on artificial vision and a module that includes a camera and Raspberry Pi 3 processor to identify, process the image and make a decision to approve or discard the product. We used the OpenCV tools and the Python language to develop the programming cod